German churches in times of demographic change and declining affiliation: A projection to 2060 - David Gutmann; Fabian Peters (Comparative Population Studies (CPoS), 2020)
The problem of declining membership in Germany's churches has been apparent for almost half a century. However, few scientific studies have investigated the respective influences of demographic and church-specific phenomena, as well as the potential impact if present trends continue. To answer these questions, we use a cohort component model and project the membership of each German Catholic diocese and Protestant regional church until 2060. Thus, for the first time we present a projection of church members for each of the 27 Catholic (arch-) dioceses and the 20 Protestant regional churches, as well as for the entire Evangelical Church and the Roman Catholic Church in Germany. We collected data from dioceses, Protestant regional churches and the Federal Statistical Office. Under the assumptions made, the results suggest a continued decline in membership and that by 2060 the number of church members would be half the number of 2017. Protestant Church membership would have shrunk slightly more than Catholic Church membership. We can conclude that church-specific factors (baptisms, leaving, and joining the church) would have a stronger influence on declining numbers than demographic factors. Moreover, demographic change would have a greater impact on registered church membership than on the total population. The proportion of Christians in the population would sharply decrease. Although in 2017 54.4 percent of the population belonged to one of the two major churches, according to the projection model, only 31.1 percent would be church members in 2060. As our results are not predictions but projections using trend analysis, we show how changed conditions would affect the projected development in five scenarios.
urn:nbn:de:bib-cpos-2020-01en3
Keywords: 300; Church membership; Demographic change; Multi-region cohort-component model; Multi-state population projection; Christianity; Roman Catholicism; Protestantism